Antibacterial activity of the Mucus Extract from the Giant African Snail (Lissachatina fulica) and Golden Apple Snail (Pomacea canaliculata) against pathogenic bacteria causing skin diseases - Nattawadee Nantarat (2020)
© 2019 by Chulalongkorn University. There have been many cases of snails reported to be agricultural pests in Thailand, including the important invasive pests, giant African snail, Lissachatina fulica, and the golden apple snail, Pomacea canaliculata. These snails have rich mucus that covers their surface, which may serve in preventing moisture evaporation, reducing friction and providing resistant to infection by microorganisms. In this study, the antibacterial activity of aqueous extracts of L. fulica and P. canaliculata mucus were tested against four strains of Gram-positive bacteria, Staphylococcus aureus, methicillin-resistant S. aureus (MRSA), Staphylococcus epidermidis and Corynebacterium sp. Thirty adult snail samples of both L. fulica and P. canaliculata were collected, snail mucus was harvested, and a crude aqueous extract of the mucus (CME) prepared. The in vitro antibacterial activity of each CME was evaluated by the agar well diffusion method, while the broth dilution method was used to determine its minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). CME from both L. fulica and P. canaliculata displayed antibacterial activity against all four strains of Gram-positive bacteria in the agar well diffusion assay. In the broth dilution assay, CME from L. fulica showed weak activity against all four bacterial strains, being highest against S. aureus and MRSA (MIC 12.5 μg/ml; MBC > 50 μg/ml), followed by S. epidermidis and Corynebacterium sp. (MIC 25 μg/ml; MBC > 50 μg/ml); however, that from P. canaliculata showed no antibacterial activity against these bacteria. Therefore, CMEs from these two snail species were somewhat effective against these pathogens, and might be useful for human healthrelated applications in the future, following further fractionation to isolate the active components and determination of their optimal concentrations, and whether or not they act synergistically.